Pengaruh model project based learning terhadap aspek dekomposisi pada kemampuan computational thinking mathematics peserta didik kelas iv di sekolah dasar - Flavionanda Amelia Azzahra; Sandra Bayu Kurniawan (Jurnal Pendidikan Dasar, 2026)
The Project Based Learning (PjBL) learning model is currently a concern in the world of education, especially in mathematics learning at the elementary school level. This study aims to examine the effect of implementing the PjBL model on the computational thinking skills of fourth grade students in mathematics. The research approach used is true experimental with a pretest-posttest control group design. The research subjects consisted of two groups, namely the experimental class that received learning with the PjBL model and the control class that followed conventional learning. The results of the analysis showed a significant difference between the computational thinking skills of students in the two groups. The effect size value of 1.418 indicates that the application of the PjBL model has a major influence on improving students' computational thinking skills. Thus, the Project Based Learning model has proven effective in developing computational thinking skills at the elementary school level.